Islamic and Scientific Views on The Law of Using Urine Samples as Candidates for Early Detection of Cancer - Prasetyo, Angga Dwi (SHAHIH: Journal of Islamicate Multidisciplinary, 2022)
Abstract The growing prevalence of cancer patients is a significant obstacle to global human growth. Prostate carcinoma is one of the types of cancer that kills the most men. The second most frequently diagnosed kind of carcinoma is prostate cancer (Pca), which is also the sixth biggest cause of death in males globally. Urine can be a candidate for early diagnosis of non-invasive cancer, however the rule on the use of urine as a sample in Islam has not yet been thoroughly addressed. Prostate cancer testing is still an intrusive procedure. The goal of this study was to ascertain the legality of using urine samples as potential candidates for the early identification of cancer from both an Islamic and scientific standpoint. Meta-analysis is combined with a qualitative methodology. According to the study's findings, urine may be a candidate for the early detection of cancer. Legally speaking, urine can be used as long as it is not applied directly to patients either topically or orally in order to prevent it from becoming haram. This is because the authors were unable to find any evidence to support the prohibition of using urine on patients.